Impact of national pandemic lockdowns on perceived threat of immigrants: a natural quasi-experiment across 23 countries - Han, Qing; Zheng, Bang; Leander, N Pontus; Agostini, Maximilian; Gutzkow, Ben; Kreienkamp, Jannis; Kutlaca, Maja; Lemay Jr., Edward P; Stroebe, Wolfgang; vanDellen, Michelle R; Collaboration, PsyCorona; Abdul Khaiyom, Jamilah Hanum; et al. (SAGE, 2022)
Xenophobia and anti-immigrant attacks rose during the COVID-19 pandemic, yet this may not be solely due to the disease threat. According to theories of frustration and scapegoating, situational obstructions and deprivation can motivate prejudice against outgroups. Using a global natural quasi-experimental design, this study tests whether the restrictiveness of national lock-downs can explain higher individual-level perceptions of immigrant threat. Data of 45,894 participants from 23 countries were analyzed. Both lockdown duration and lockdown severity were positively associated with individuals’ perceived threat of immi-grants. The lockdown effects were independent of objective and subjective measures of disease threat, and there was no evi-dence that disease threat drives people’s prejudice toward immigrants. Subgroup analysis suggested the lockdown effects were reliable in Europe and the Americas, but not in Asia. These findings suggest a need to mitigate frustration and scapegoating when implementing lockdowns, and to distinguish the influence of societal restrictions from disease threat.